Sphingosine 1‐phosphate and its carrier apolipoprotein M in human sepsis and in Escherichia coli sepsis in baboons. Issue 6 (17th March 2016) - Frej, Cecilia; Linder, Adam; Happonen, Kaisa E.; Taylor, Fletcher B.; Lupu, Florea; Dahlbäck, Björn
Abstract: Sphingosine 1‐phosphate (S1P) is an important regulator of vascular integrity and immune cell migration, carried in plasma by high‐density lipoprotein (HDL)‐associated apolipoprotein M (apoM) and by albumin. In sepsis, the protein and lipid composition of HDL changes dramatically. The aim of this study was to evaluate changes in S1P and its carrier protein apoM during sepsis. For this purpose, plasma samples from both human sepsis patients and from an experimental Escherichia coli sepsis model in baboons were used. In the human sepsis cohort, previously studied for apoM, plasma demonstrated disease‐severity correlated decreased S1P levels, the profile mimicking that of plasma apoM. In the baboons, a similar disease‐severity dependent decrease in plasma levels of S1P and apoM was observed. In the lethal E. coli baboon sepsis, S1P decreased already within 6–8 hrs, whereas the apoM decrease was seen later at 12–24 hrs. Gel filtration chromatography of plasma from severe human or baboon sepsis on Superose 6 demonstrated an almost complete loss of S1P and apoM in the HDL fractions. S1P plasma concentrations correlated with the platelet count but not with erythrocytes or white blood cells. The liver mRNA levels of apoM and apoA1 decreased strongly upon sepsis induction and after 12 hr both were almost completely lost. In conclusion, during septic challenge, the plasma levels of S1P drop to very low levels. Moreover, the liver synthesis of apoM decreases severely and the plasma levels of apoM are reduced. Possibly, the decrease in S1P contributes to the decreased endothelial barrier function observed in sepsis.